Lay Up Shoot Technique in Basketball Games - Ishak, Muhammad; Sahabuddin, Sahabuddin (Sains Global Institut, Indonesia, 2023)
This research aims to determine the relationship between leg explosive power, wrist flexibility, and hand-eye coordination on lay-up shooting ability. This type of research is a type of descriptive research. The research variables consist of independent variables, namely leg explosive power, wrist flexibility, and hand-eye coordination, while the dependent variable is lay-up shooting ability. The population in this study were all BKMF FIK UNM college college students with a research sample of 30 people. The sampling technique is to use